Timeline: A web application for assessing the timing and details of health behaviors. (4th March 2019) - Wray, Tyler B.; Adia, Alexander C.; Pérez, Ashley E.; Simpanen, Erik M.; Woods, Laura-Allison; Celio, Mark A.; Monti, Peter M.
ABSTRACT: Background : Timeline Followback (TLFB) interview methods are used to assess a variety of health behaviors, including alcohol use, drug use, and sexual behavior. While several online TLFBs have been developed, most focus on single behaviors, and few studies have explored their validity in assessing multiple risk behaviors using a single online TLFB. Objective : To examine the validity of a customizable web application (Timeline) for assessing alcohol use, drug use, and sexual behavior among high-risk men who have sex with men. Methods : Participants ( N = 15 men) completed standardized survey instruments before undergoing a 30-day daily diary procedure where they submitted daily reports of health risk behaviors via smartphone. They then completed a Timeline at the end of the 30-day period covering the same time interval. Results : Comparing a baseline administration of Timeline with popular surveys of health risk behaviors supported Timeline's validity ( r = 0.41–0.59 for alcohol use, r = 0.83 for drug use, and r = 0.34–0.52) for sexual behaviors. While participants reported similar amounts of each behavior via daily diary as they did on a follow-up Timeline ( r = 0.55–0.88 for alcohol use, r = 0.69 for drug use, and r = 0.87–0.92 for sexual behaviors), results provided evidence of underreporting on the Timeline. Timing of behaviors also frequently disagreed across these methods. Conclusions : Timeline is valid for assessing overall engagement in alcohol use, drug use, and sexual behavior over a 30-day window. However, researchers interested in the specific timing of behaviors within assessment intervals should use smaller follow-up intervals (e.g., 7 days, 14 days) or more intensive reporting methods (e.g., daily diary).